Antimalarials and the fight against malaria in Brazil - Luiz MA Carmargo; Saulo de Oliveira; Sergio Basano; Célia RS Garcia (Dove Medical Press, 2009)
Luiz MA Carmargo1, Saulo de Oliveira2, Sergio Basano3, Célia RS Garcia21ICBV-USP, Monte Negro, Rondônia, Brasil; 2Departamento de Fisiologia, Instituto de Biociências, Universidade de São Paulo, SP, Brazil; 3CEMETRON, Porto Velho, Guaporé, BrazilAbstract: Malaria, known as the “fevers,” has been treated for over three thousand years in China with extracts of plants of the genus Artemisia (including Artemisia annua, A. opiacea, and A. lancea) from which the active compound is artemisin, a sesquiterpene that is highly effective in the treatment of the disease, especially against young forms of the parasite. South American Indians in the seventeenth century already used an extract of the bark of chinchona tree, commonly named “Jesuits’ powder.” Its active compound was isolated in 1820 and its use spread all over the world being used as a prophylactic drug during the construction of the Madeira–Mamoré railroad in the beginning of the twentieth century. During the 1920s to the 1940s, new antimalarial drugs were synthesized to increase the arsenal against this parasite. However, the parasite has presented systematic resistence to conventional antimalarial drugs, driving researchers to find new strategies to treat the disease. In the present review we discuss how Brazil treats Plasmodium-infected patients.Keywords: Plasmodium falciparum, malaria, antimalarials, calcium